Cartografias do Armário: estratégias do desejo em uma cidade do interior paulista - Santos, Daniel Kerry dos; Teixeira Filho, Fernando Silva [UNESP] (My University, 2014)
This article aims to present the results of a research about the links among homophobia, subjectivation processes and constructions of gender and sexual identities in a small city in the interior of São Paulo State. The main research question that guided us was: how homophobia regulates the desire and the “transit between the closets” among the so called gay people in a small city? To answer that question we made interviews that were analyzed and transformed into narratives of four cisgender men of different ages who call themselves homosexual or who have had homoerotic practices with other men. All participants live in the same city, do not know one another and have lived most of their lives city. We have problematized how these participants gave meaning to the experiences of regulation of their sexuality that have been aroused by homophobia and by the device of closet. Analyses indicated that the 'closet' can both regulate and oversee their lives, limiting their possibilities of desiring, but also may raise resistance, from which it is possible to establish a relationship with another ethical life, that is, producing other ways of life in the small city.

Esse artigo é resultado de uma pesquisa sobre as articulações entre homofobia, processos de subjetivação e construções de identidades de gênero e sexual em uma cidade do interior paulista . A pergunta que nos norteou durante o percurso foi: de que modo a homofobia regula o desejo e o trânsito “entre os armários” de pessoas ditas homossexuais em uma cidade do interior? Trata-se de uma cartografia realizada a partir de entrevistas transformadas em narrativas de quatro homens cisgêneros de idades distintas que se autodenominam homens homossexuais ou experienciam práticas homoeróticas. Todos os participantes residem na mesma cidade, não se conhecem e viveram a maior parte de suas vidas nela. Procuramos problematizar o modo como estes participantes deram sentido às experiências de regulação de suas sexualidades decorrente da homofobia e do dispositivo do armário. As análises indicaram que o armário tanto pode regular e vigiar suas vidas, restringindo possibilidades desejantes, como também pode suscitar resistências, a partir das quais é possível estabelecer uma outra relação ética com a vida, isto é, produzir outros modos de vida possíveis na cidade.
Cartographies of the Closet: strategies of desire in an interior city of the State of São Paulo
Keywords: Homosexuality; Homophobia; Closet; Subjectivation; Interior city; Desire; Homossexualidade; Homofobia; Armário; Subjetivação; Cidade do interior; Desejo